Prosocial behavior and public service motivation - Esteve, Marc et al (2016)
Although research on public service motivation (PSM) is vast, there is little evidence regarding the effects of PSM on observable behavior. This article contributes to the understanding of the behavioral implications of PSM by investigating whether PSM is associated with prosocial behavior. Moreover, it addresses whether and how the behavior of other group members influences this relationship. The article uses the experimental setting of the public goods game, run with a sample of 263 students, in combination with survey-based PSM measures. A positive link is found between PSM and prosocial behavior. This relationship is moderated by the behavior of other group members: high-PSM people act even more prosocially when the other members of the group show prosocial behavior as well, but they do not do so if the behavior of other group members is not prosocial. 11
Keywords: Social behaviour; Public utilities; Motivation